PENGARUH FUNDAMENTAL MAKROEKONOMI TERHADAP PENANAMAN MODAL ASING DI ASEAN - Kristianto, Andriyan; Zuhroh, Idah; Anindyntha, Firdha Aksari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
This study aims to see the effect of macroeconomics fundamental that proxied by economic growth, inflation and interest rates on foreign investment in ASEAN 5. This research uses panel data regression analysis. The data source is from World Bank that are consist of Foreign Direct Investment, Gross Domestic Product, inflation, and interest from 2007 to 2022. The results show that the Gross Domestic Product has a positive effect on Foreign Direct Investment. Meanwhile, the inflation and interest rates have a negative effect on Foreign Direct Investment